2020
DOI: 10.1002/mds.28221
|View full text |Cite
|
Sign up to set email alerts
|

High γ‐Aminobutyric Acid Content Within the Medial Prefrontal Cortex Is a Functional Signature of Somatic Symptoms Disorder in Patients With Parkinson's Disease

Abstract: Background: The dysfunctional activity of the medial prefrontal cortex has been associated with the appearance of the somatic symptom disorder, a key feature of the Parkinson's disease (PD) psychosis complex. Objectives: The objectives of this study were to investigate whether the basal contents of inhibitory γ-aminobutyric acid and excitatory glutamate plus glutamine neurotransmitter levels are changed in the medial prefrontal cortex of patients with PD with somatic symptom disorder and whether this alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 82 publications
2
15
0
Order By: Relevance
“…Recently, we have reported that increased γ‐aminobutyric acid (GABA) content in mPFC is a neural feature of SSD, regardless of PD comorbidity. It has also been proposed that GABA levels within the mPFC are critical to shaping the strength of its functional connectivity in healthy subjects 29‐32 . However, it is currently unknown whether the altered inhibitory neurotransmission observed in SSD is associated with altered patterns of mPFC functional connectivity and whether these effects are similarly found in SSD patients with or without PD.…”
mentioning
confidence: 99%
“…Recently, we have reported that increased γ‐aminobutyric acid (GABA) content in mPFC is a neural feature of SSD, regardless of PD comorbidity. It has also been proposed that GABA levels within the mPFC are critical to shaping the strength of its functional connectivity in healthy subjects 29‐32 . However, it is currently unknown whether the altered inhibitory neurotransmission observed in SSD is associated with altered patterns of mPFC functional connectivity and whether these effects are similarly found in SSD patients with or without PD.…”
mentioning
confidence: 99%
“…Depression is also characterized by deficits of excitatory glutamate neurons and inhibitory GABA interneurons ( Duman et al, 2019 ). Evidence of associations between glutamate and/or GABA levels and fMRI signal was found recently ( Delli Pizzi et al, 2020 ; Demartini et al, 2020 ; Kiemes et al, 2021 ). Therefore, characterization of the altered cortical neural activities in PD patients with depression is of great significance to help better understand the pathology underlying it, which can help optimize the design of therapeutic strategies and protocols for PD patients with depression.…”
Section: Introductionmentioning
confidence: 81%
“…A recent study highlighted that elevated GABA levels within the medial prefrontal cortex were associated with somatic symptom disorder in subjects with and without PD. 20 GABA alterations might also contribute to axial symptoms, which typically show poor response to dopaminergic treatment. 21 On the contrary, van Nuland and colleagues did not find a significant impact of GABA levels on tremor in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Yet the biological meaning remains poorly understood. A recent study highlighted that elevated GABA levels within the medial prefrontal cortex were associated with somatic symptom disorder in subjects with and without PD 20 . GABA alterations might also contribute to axial symptoms, which typically show poor response to dopaminergic treatment 21 .…”
Section: Discussionmentioning
confidence: 99%